Dynamics of Tethered Satellite Systems. - Aslanov, V. S. (Woodhead Publishing in mechanical engineering., 2012)
Aimed at engineering students and professionals working in the field of mechanics of space flight, this book examines space tether systems - one of the most forward-thinking directions of modern astronautics. The main advantage of this technology is the simplicity, profitability and ecological compatibility: space tethers allow the execution of various manoeuvers in orbit without costs of jet fuel due to the use of gravitational and electromagnetic fields of the Earth. This book will acquaint the reader with the modern state of the space tether's dynamics, with specific attention on the resear.